Companhia Teatro Moderno de Lisboa (TML): engagement, resistance and cultural creation in the 1960s - Paranhos, Kátia Rodrigues (Seven Editora, 2023)
Social theatre and politically engaged theatre are two designations that gained acceptance amid a lively debate that went on throughout the late 19th century and consolidated in the 20th century. Its turning point lay in the structure of the relations between theatre and politics or even between theatre and propaganda. This text addresses what resistance and political-cultural protest meant to Grupo Teatro Moderno de Lisboa (TML), from Lisbon/Portugal, in the 1960s, based on the interviews and discourses about their collective creation processes, theoretical research, and social intervention. According to many interpreters, the Group broke with the theater establishment of 1960 and came out as one generation's great movement. It only lasted for 4 years, from 1961 to 1965. During this time, TML staged theatrical texts by Carlos Muniz, Dostoyevsky, Miguel Mihura, John Steinbeck, Luiz Francisco Rebello, William Shakespeare, and José Carlos Pires. These artists made up and remade different universes according to their purposes and wishes. By reading the above authors' texts in the 1960s, these Portuguese artists gave new meanings to the present and to the past itself – recalling here Brecht's "past and present in one". The political and aesthetic issues in the plays were updated through debates between the theater group and the audience —quite a difficult task in a period when a political-cultural protest against the "Estado Novo" dictatorship was increasingly strong and constant, and in which official censorship, always vigilant against heterodox artistic manifestations, was stifling. Being active in the politically engaged theater then meant looking for different staging places and other points of view on the years of lead. Utilizing its actions, it is a ground principle, and its practices, TML would sow the seeds of the independent theatre group movement, having taken the first steps in the pathway toward an intervention theater that, later on, these groups took upon themselves to continue with.Despite adversities, theatrical experiments that go against the grain of prevailing thoughts are still tenaciously current on the agenda. Doing theater amid commercial pressure is, undoubtedly, a form of provocation, of insubordination to the "hit parade" market, to which Comuna – Teatro Pesquisa, Teatro da Cornucópia, O Bando, Casa da Comédia, A Barraca, the Évora Culture Center and SeivaTrupestill resort.DOI: https://doi.org/10.56238/devopinterscie-081